2005
DOI: 10.1097/01.prs.0000163321.83155.5a
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medial Arm Skin as a Free Flap

Abstract: A medial arm free flap is a plausible reconstructive option with good knowledge of the anatomical variations, as the defect on the medial arm is cosmetically more acceptable and has a better color match for head and neck reconstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 12 publications
1
21
0
7
Order By: Relevance
“…Through the anastomotic connection between the PURA and superior ulnar collateral artery (SUCA), the PURA can reliably perfuse the medial arm skin via one or two cutaneous perforators arising from the SUCA [3]. Anatomic studies have demonstrated that there exists a row of five or six cutaneous perforator arteries along the medial intermuscular septum in the medial arm [4][5][6][7]. Based on the work of Maruyama et al, we postulate that there exists the phenomenon of one perforator artery perfusing multiple perforator angiosomes in the medial arm.…”
Section: Introductionmentioning
confidence: 99%
“…Through the anastomotic connection between the PURA and superior ulnar collateral artery (SUCA), the PURA can reliably perfuse the medial arm skin via one or two cutaneous perforators arising from the SUCA [3]. Anatomic studies have demonstrated that there exists a row of five or six cutaneous perforator arteries along the medial intermuscular septum in the medial arm [4][5][6][7]. Based on the work of Maruyama et al, we postulate that there exists the phenomenon of one perforator artery perfusing multiple perforator angiosomes in the medial arm.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, su existencia también puede ser beneficiosa, ya que es más accesible para realizar una adecuada cateterización (Patnaik et al) o puede ser útil como arteria que nutra un injerto libre de la región braquial medial (Karamürsel et al, 2005).…”
Section: Introductionunclassified
“…Another study determined that the medial arm skin blood supply originates from the superior ulnar collateral artery, direct cutaneous artery, brachial artery and the superficial brachial artery [22]. An anatomic study determined that there are two areas, 7.5 and 8.2 cm, proximal to the medial epicondyle in the medial arm.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomic studies have been made related to define the localization of the flap perforators [8,[20][21][22]. However, it is still not known exactly how much tissue can be supplied proximally with these perforators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation